Australia : 2016 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Australia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights that Australia has enjoyed robust growth despite the commodity price and mining investment bust. The moderate impact of the large shocks since 2011 highlights the resilience of the economy and strong policy frameworks. Recent structural reforms have focused on fostering innovation. The National Innovation and Science Agenda includes measures to boost innovation and entrepreneurship in the high-tech sector, including through tax breaks. Legislation is being prepared for key components of the Harper Review, which has identified a number of reforms to boost competition and productivity in the services sectors, and to strengthen competition policy broadly.